2014
DOI: 10.1038/ng.2953
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genomic characterization of adrenocortical carcinoma

Abstract: Adrenocortical carcinomas (ACCs) are aggressive cancers originating in the cortex of the adrenal gland. Despite overall poor prognosis, ACC outcome is heterogeneous. We performed exome sequencing and SNP array analysis of 45 ACCs and identified recurrent alterations in known driver genes (CTNNB1, TP53, CDKN2A, RB1 and MEN1) and in genes not previously reported in ACC (ZNRF3, DAXX, TERT and MED12), which we validated in an independent cohort of 77 ACCs. ZNRF3, encoding a cell surface E3 ubiquitin ligase, was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
756
3
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 568 publications
(834 citation statements)
references
References 71 publications
35
756
3
21
Order By: Relevance
“…CTNNB1 alterations in sinonasal HPC have been consistently reported in exon 3, with missense mutations [4,5]; mutations affecting positions 32-45 of the amino-terminal region disrupt phosphorylation-dependent degradation of b-catenin [6]. Numerous other tumor types harbor CTNNB1 mutations, most frequently desmoid-type fibromatosis [7,8] as well as salivary basal cell adenoma [9], pilomatricoma and pilomatrix carcinoma [10], hepatocellular carcinoma [11], colorectal carcinoma [12], medulloblastoma [13], endometrial adenocarcinoma [14], Wilms tumor [15], and adrenocortical carcinoma [16]. Sinonasal HPC shares the features of a uniform spindle and ovoid cell population and HPC-like vessels with SFT, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CTNNB1 alterations in sinonasal HPC have been consistently reported in exon 3, with missense mutations [4,5]; mutations affecting positions 32-45 of the amino-terminal region disrupt phosphorylation-dependent degradation of b-catenin [6]. Numerous other tumor types harbor CTNNB1 mutations, most frequently desmoid-type fibromatosis [7,8] as well as salivary basal cell adenoma [9], pilomatricoma and pilomatrix carcinoma [10], hepatocellular carcinoma [11], colorectal carcinoma [12], medulloblastoma [13], endometrial adenocarcinoma [14], Wilms tumor [15], and adrenocortical carcinoma [16]. Sinonasal HPC shares the features of a uniform spindle and ovoid cell population and HPC-like vessels with SFT, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These have paved the way for further studies attempting to correlate these profiles with clinical outcomes [17,35,36]. Notably, more recent integrated genomic analyses involving exome sequencing, DNA methylation analysis, mRNA expression arrays, and miRNA sequencing have suggested that aggressive and indolent ACCs belong to two distinct molecular entities, each spearheaded by separate oncogenic mutations [16]. Despite these advances in knowledge of the underlying molecular pathology of ACCs, there has been a paucity of data on immunohistologically validated markers.…”
Section: Discussionmentioning
confidence: 99%
“…Missense mutations of MED12 are associated with X-linked genetic syndromes [103][104][105]. Somatic mutations have been described in many solid tumors, including, hormone-associated cancers (prostate and adrenocortical carcinoma) [106,107], breast [108], uterine tumors [109]. The mutations are essentially missense mutations but fall in different parts of the protein, depending on the tumors.…”
Section: Med12 Mutationsmentioning
confidence: 99%